Interdisciplinarity in the dissertations of an Interdisciplinary Graduate Program in Human Sciences: challenges and possibilities - De Conto, Júlia Carolina Vizzotto (2023)
The aim of this article was to analyze the dissertations of the Programa de Pós-graduação Interdisciplinar em Ciências Humanas (PPGICH), defended between 2017 and 2022, in order to identify if and how interdisciplinarity is mentioned and conceptualized in the dissertations of this Program. The research took place through a survey of the dissertations of the Program in the digital repository of the university itself. The analysis of the PPGICH dissertations revealed that, among the 86 dissertations with access available in the repository, only 33 of them mention the word “interdisciplinarity” in the body of the text. In addition, only 17 of these dissertations present a clear conceptualization of the term. The low presence of the conceptualization of interdisciplinarity in student research points to the need for greater attention and reflection on this fundamental theme in the referred graduate program, since it brings the interdisciplinary in its own name.